2007
DOI: 10.1111/j.1440-1681.2007.04714.x
|View full text |Cite
|
Sign up to set email alerts
|

REVERSAL OF CISPLATIN‐INDUCED CARNITINE DEFICIENCY AND ENERGY STARVATION BY PROPIONYL‐l‐CARNITINE IN RAT KIDNEY TISSUES

Abstract: 1. The present study examined whether propionyl-L-carnitine (PLC) could prevent the development of cisplatin (CDDP)-induced acute renal failure in rats. 2. Forty adult male Wistar albino rats were divided into four groups. Rats in the first group were injected daily with normal saline (2.5 mL/kg, i.p.) for 10 consecutive days, whereas the second group received PLC (250 mg/kg, i.p.) for 10 consecutive days. Animals in the third group were injected daily with normal saline for 5 consecutive days before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 60 publications
7
27
0
Order By: Relevance
“…Treatment with L-carnitine before the CDDP challenge could significantly prevent the depletion of the kidney and liver antioxidant systems. Similar results have been reported by Aleisa et al [14], Al-Majed et al [15], and Arafa HM [41] for kidney and liver tissues in which cisplatin and carboplatin injections caused low GSH, GSH-Px, SOD, and nitric oxide levels. Furthermore, in this study, it was observed that levels of GSH-Px and SOD for CDDP in the L-carnitine-treated groups were higher than in the CDDP group.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Treatment with L-carnitine before the CDDP challenge could significantly prevent the depletion of the kidney and liver antioxidant systems. Similar results have been reported by Aleisa et al [14], Al-Majed et al [15], and Arafa HM [41] for kidney and liver tissues in which cisplatin and carboplatin injections caused low GSH, GSH-Px, SOD, and nitric oxide levels. Furthermore, in this study, it was observed that levels of GSH-Px and SOD for CDDP in the L-carnitine-treated groups were higher than in the CDDP group.…”
Section: Discussionsupporting
confidence: 79%
“…It is synthesized endogenously from the essential amino acids lysine and methionine. In fact, carnitine effectively inhibits mitochondrial damage induced by oxidative stress, as well as mitochondriadependent apoptosis in various types of cells [13,14]. The effects of LC on the metabolism of tissues in organs such as the heart [15], brain [16], and liver [13] have been studied widely.…”
Section: Introductionmentioning
confidence: 99%
“…Aleisa et al [13] reported that the administration of propionyl L-carnitine at a dose of 250 mg/kg (i.p.) significantly attenuated the nephrotoxic effects of cisplatin, which manifested as a normalization of the cisplatin-induced increase in thiobarbituric acid reactive substances, such as MDA and nitric oxide, and the cisplatin-induced decrease in reduced glutathione in rat kidney tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous L-carnitine is synthesized from lysine and methi- onine primarily in the liver, as well as in the kidneys and brain tissue [24]. Previous studies have indicated that L-carnitine has an important role in oxidative/antioxidative balance as well as in the transport function of long-chain fatty acids into the mitochondria in biological systems [12][13][14][15]. However, the effects of L-carnitine on specific antioxidant enzymes, such as GPX, CAT and MPO, which detoxify H 2 O 2 in water, have been reported independently in a few studies [14,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation